Rancang Bangun Pengukur Persentase Lemak Tubuh, Suhu Tubuh, dan Kadar Oksigen dalam Darah Berbasis IoT - Fadhillah, Muhammad; Kullaha, Razila; Sulistyo, Eko; Silalahi, Parulian (Manutech : Jurnal Teknologi Manufaktur, 2024)
This research aims to design a multifunctional device based on the Internet of Things (IoT) that utilizes Bioelectrical Impedance Analysis (BIA) method to simultaneously measure body fat percentage, body temperature, and blood oxygen levels. The device is equipped with a bioimpedance sensor to measure body fat percentage, as well as integrated temperature and oxygen sensors to detect body temperature and blood oxygen levels. Testing the device yielded highly satisfactory results with a high level of accuracy, including weight at 99.32%, height at 99.83%, body fat percentage at 97.96%, non-fat mass at 97.45%, total body water at 99.86%, body temperature at 98.61%, and oxygen levels at 99.83%. Measurement results are displayed on an LCD screen and transmitted to the Telegram application through the IoT platform. By integrating BIA, IoT, and multi-functional sensors, it is anticipated that this device can provide accurate and integrated measurements, contributing to more effective health monitoring.